Internet banking. - Lee, Hwei San. (2008)
With globalisation and liberalisation of the banking sector, the Internet has become an important source of delivery channel. To become global players, banks have to take a pro-active approach in their Internet banking initiatives. Although Internet banking in Singapore still has a long way to go, future prospects are optimistic.